Formulative Policy of Death Penalty for Corruptors in Indonesia - Ni Wayan SINARYATI; I Gede ARTHA (Prizren Social Science Journal, 2020)
Corruption is committed by state officials, law enforcement and other related parties. Various efforts have been made by the government in preventing and eradicating corruption in Indonesia, but the efforts that have been made have not yet gotten optimal results. The fundamental weakness in eradicating corruption in Indonesia is the formulation of the main criminal sanctions in the form of criminal threats that are facultative, uncertain or must be. So that the corruptors are never deterred or afraid. In the future, the legislators need to reformulate the provisions of Article 2 paragraph (2) of the Republic of Indonesia Law Number 31 of 1999 as amended to Law of the Republic of Indonesia Number 20 of 2001 concerning Eradication of Corruption. Various criminal law policies still need to be carried out by the state in order to eradicate corruption to achieve the expected results. This type of research in this paper uses the type of normative legal research. The type of approach is in the form of a legal approach related to corruption. There are two legal materials used, namely primary legal materials and secondary legal materials, with legal material collection techniques used in the form of library studies. The analysis technique used is descriptive, interpretation, evaluation and argumentative techniques. The research in this paper intends and aims to examine and analyze the facts and phenomena of corruption that are stated in specific legislation concerning criminal sanctions (capital punishment) for corruptors in Indonesia. Moreover, corruption is qualified as an extraordinary crime so it needs extraordinary handling as well.